Proximate Test and Organoleptic Test on the Characteristics of the Moringa Layer Cake - Cici Wulandari; Budaraga IK; Wellyalina Wellyalina; Napassawan Liamnimitr (Lembaga Penelitian dan Pengabdian, Universitas Andalas, 2020)
Tradisional food from Indonesian that is a layer cake. Layer cake is usually made in with many variant colour. Beside that a layer cake made by rice powder, wheat powder, and starch powder. The taste is chewy, legit, and sweet making this cake liked by all circles. The purpose is to know a quality of layer cake with adding moringa leaf powder and adding moringa leaf powder with treatmet 5 test and 3 times test. The resull of analysis using anova with test and continve test Duncan’s New Multiple Range Test (DMNRT). The resull showing if adding moringa leaf power have infiuence with a layer cake quality and adding moringa leaf power in organoleptik fase into a layer cake is two percent (2%).